In How Far is Elckerlijc Dutch? References to the Dutch Origin in the Polish Reception of the Middle Dutch Text - Dowlaszewicz, Małgorzata (Werkwinkel, 2016)
The sixteenth-century morality play Elckerlijc is one of the few texts mentioned in almost all Dutch canon lists. It is no surprise that this is one of the few medieval Dutch texts transferred into different languages and cultures. There are two Polish texts based on it, the first from 1921 by Jarosław Iwaszkiewicz (Kwidam), the second from 1933 by Stanisław Helsztyński (Każdy (Everyman): średniowieczny moralitet angielski). The text was though never directly translated into Polish from Dutch. The main issue is whether these translations have influenced the image of Dutch literature in Poland. It appears that secondary literature has seen the plays of Iwaszkiewicz and Helsztyński only as transfer of German or English literature and ideas and that it is rarely known that the original story originates from the Netherlands.